Efektivitas Pelatihan Workshop Laboratorium Terhadap Asisten Laboratorium di Fakultas Pertanian UNS - Sri Liswardani; S Sulistyo; Choirul Anam (Jurnal Pengelolaan Laboratorium Pendidikan, 2022)
The laboratory is one of the strategic supporting elements of academic activities in universities. The laboratory is a means for students and lecturers to carry out educational, research, and community service activities. Laboratory users are practicum students, research and lecturers. For this reason, it is necessary to make a special strategy, namely providing provisions for practical assistants. In practicum assistants have a role of almost 85% in the practicum process, so the intensity of assistants with students is much more. The purpose of the study was to measure the effectiveness of assistant training through lab workshops to increase their competence by providing sufficient knowledge about knowledge of laboratory equipment, chemicals and occupational safety and health (K3) in the laboratory for practical assistants in the Laboratory of Animal Husbandry Study Program and Science Study Program. Food Technology, Faculty of Agriculture, UNS. The target for the achievement of this research activity is that the practical eye assistant has knowledge of knowledge of laboratory equipment, chemicals and K3 in the laboratory in a laboratory environment. The method of carrying out the activities is carried out in three procedures, namely (1) pretest and posttest, (2) briefing and discussion, and (3) training and practice on knowledge of laboratory equipment, chemicals and K3 in the laboratory. Data analysis used descriptive analysis, paired sample t-test. The results of this study obtained that the mean or average before the workshop was 86.67 and after the workshop was 90.86 it was very clear that there was an increase in the knowledge of lab assistants after the laboratory workshop. It can be concluded in this study that the training of assistants through lab workshops can be useful for practical eye assistants, increasing their competence in knowledge of laboratory equipment, chemicals and occupational safety and health (K3) in the laboratory at the Laboratory of Animal Husbandry Study Program and Technology Science Study Program. Food Faculty of Agriculture UNS.